Intersectional inequalities in exclusive breastfeeding practices in India: analysis of national family health survey-4 - Haseena Chekrain Valappil; Rajeev Jayalakshmi; Christian Sewor (BMC, 2023)
Abstract Background Exclusive breastfeeding in the initial six months of infancy plays a significant role in the physical and cognitive development of the child. One in two children below six months of age in India is not receiving exclusive breastfeeding, with the rates varying considerably between and within states. In this study, we investigated the effect of intersecting inequalities in exclusive breastfeeding practice amongst children below six months in India. Methods Data from the fourth National Family Health Survey (NFHS-4) was used for the study. The study used a weighed sample of 211,145 infants below six months. Exclusive breastfeeding practice was assessed based on the previous 24-hours feeding practice of the child. Intersecting social categories were created based on place of residence, religion, wealth index, and mothers' education. A binary logistic regression model was used to explore inequalities in the practice of exclusive breastfeeding based on the intersecting social categories. Results Exclusive breastfeeding practices varied significantly between the intersecting categories of religion, place of residence, wealth index, and education of the mother. Exclusive breastfeeding practice prevalence was the highest amongst children born in the Urban-Secondary-Poor-Others group (57.9%) and lowest amongst the Rural-Primary-Rich-Others category (34.5). In comparison to children in the most disadvantaged category (Rural-Primary-Poor-Others), children born in the Rural-Secondary-Poor-Others category had the highest odds [OR (odds ratio) 1.213; 95% CI 1.024, 1.437] of being exclusively breastfed, whilst children within the Rural-Primary-Rich-Others category had the lowest odds (OR 0.494; 95% CI 0.345, 0.708). Wide disparities were observed in the odds of engaging in exclusive breastfeeding practice amongst the middle groups than between the most advantaged and the most disadvantaged groups. The inequality indices show varied distribution of exclusive breastfeeding prevalence across the intersecting groups with higher exclusive breastfeeding prevalence noted amongst disadvantaged groups. Conclusions The study found that intersecting inequalities in exclusive breastfeeding exist in India. In order to improve exclusive breastfeeding practice, targeted interventions must acknowledge and adopt a comprehensive approach that addresses inherent inequalities resulting from the intersection of various axes of social stratification.